COMPUTATIONAL STUDY ON POLYMERS OF UNSUBSTITUTED AND SOME SUBSTITUTED PYRROLES (2015)
Conjugated polymers which interact with biological systems have attracted interest due to their high conductivity, stability and electronic properties. Substituted polymers of 3-methyl pyrrole-4-carboxylic acid (MPCa) have been synthesised and used as components of biosensor, while unsubstituted polypyrroles are not effective for such application. However the mechanism of interaction, nature, the relative importance of dynamic and static electron correlation of the polymers are not completely understood. This research was designed using computational approach to study the molecular properties of substituted and unsubstittued pyrrole polymers with a view to understanding what make polymers of substituted pyrroles suitable components of biosensor. Structures of unsubstituted Pyrrole (Py); substituted pyrroles which include 3-methyl- pyrrole-4-carboxylic acid (MPCa), 3-methyl-pyrrole-4-carboxamide (MPCam), 3- methyl-pyrrole-4-sulfonic acid (MPSO3H), 3-methyl-pyrrole-1-carboxylic acid, (MPCb), 3-methyl-pyrrole-4-carbothioic acid (MPCOSH), 3-methyl-pyrrole-4- carbaldehyde (MPCHO) and their polymers were studied using quantum mechanical approach. The molecular properties investigated were Energy gap (Eg), Koopman’s reactivity descriptors, Fukui function, Lowest Unoccupied Molecular Orbital (LUMO), Highest Occupied Molecular Orbital (HOMO) and thermodynamic properties. These were calculated using restricted hybrid density functional theory with Becke three, Lee Yang and Parr at 6-31G(d) basis set. The calculated Eg were extrapolated to polymer through second order-degree polynomial equation. Spin-flip time density functional theory and coupled cluster single and double method with 6-311++G(d,p) basis set were used to calculate Coupled Cluster operator (T1) diagnostic and Vertical Singlet- Triplet (VST) gap to accurately determine polymers suitability as components of biosensor. All calculations were carried out using quantum mechanical software. The calculated Eg of the polymers decreased with increasing chain length and the nature of substituent. The order of Eg was MPCHO > Py > MPCb > MPCa > MPCam > MPSO3H > MPCOSH, with MPCOSH having the lowest value of 1.7 eV. Substituted polypyrroles except MPCHO have stronger electron-electron interactions since electron-electron interaction is more when the Eg is low (between 1.0 and 3.0 eV). Koopman’s reactivity descriptors were within the range of -3.9 to 2.4 eV (chemical i potential), 1.5 to 2.1 eV (chemical hardness) and 1.4 to 4.4 eV (electrophilicity index). Fukui function revealed a high electron density around the substituted functional groups and the LUMO and HOMO were extended over the C-C and C=C bonds. Thermodynamic parameters were enthalpy change (-4361.1 to -1045.7 kJmol-), entropy change (540.3 to 952.2 Jmol-1K-1) and free energy change (∆G0f) (-4361.2 to - 1045.8 kJmol-1) indicating spontaneous formation of the polymers. The T1 diagnostic of unsubstituted polypyrroles ranged from 0.0015 to 0.0013, while substituted polypyrroles ranged from 0.030 to 0.065. The T1 <0.02 indicated that unsubstituted polypyrrole had dynamic correlation with single reference (closed shell), while T1 >0.02 showed that substituted polypyrroles possessed static electron correlation with multireference (open shell) nature. The VST gap of unsubstituted polypyrroles ranged from 3.0 to 4.8 eV, while substituted polypyrroles ranged from 3.1 to 5.3 eV. The VST gap >0 revealed that all studied systems have a singlet ground state. The presence of substituents on polypyrrole decreased the energy gaps which led to the enhancement of their molecular properties making them suitable components of biosensor.